Mangrove Crab (Scylla olivacea) Population in The Waters of The Mangrove Area, Sei Lepan Subdistrict, Langkat District, North Sumatera - Damayanti, Ervina; Jayanthi , Sri; Wahyuni, Ayu (Jurnal Biologi Tropis, 2024)
Mangroves are a habitat for mangrove crabs, one of which is Scylla olivacea, which is a source of protein and has nutritional value and is a food commodity whose selling value increases every year. The aim of this research was to determine crab density, crab growth patterns and physical and chemical condition parameters. Determining the location of the station used purposive sampling at 3 observation research locations, at each observation location 10 traps were placed. The data analysis used is data on crab density, growth patterns and environmental physico-chemical factors. This research was conducted in August 2023. There were 18 Scylla olivacea crabs that were obtained at station 1, 6 (3 males, 3 females), station 2, 5 (1 female, 4 males), station 3, 7 (3 male, 4 female), with a density value of 1800 ind/ha. The growth pattern for male mud crabs is W = 0.0202x + L5.9649 with a value for females of W = 0.0243x L+5.8572, while at all observation stations W= 0.0191x+L 6.2536. So the growth pattern of Scylla olivacea is negative allometric. Environmental parameter data consists of temperature, salinity and pH. At salinity 10 0/00 - 20 0/00 and temperature ranging from 24 0 C- 27 0 C, pH ranges from 7.1-7.3.